2018
DOI: 10.30743/aicll.v1i1.34
|View full text |Cite
|
Sign up to set email alerts
|

Problems in Multicultural Society: From Language Politeness to Hate Speech

Abstract: Indonesia is known as a nation that has many privileges such as cultural diversity and local wisdom. Cultural diversity that includes ethnic, linguistic and religious diversity is a gift and grace from God Almighty that must be managed and well maintained by all elements of the nation. Caring for diversity and harmonization in multicultural society in the era of information technology or globalization is the biggest challenge of the day. The goal is to maintain harmony and unity in the midst of a multicultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…This condition has destructive power because it spreads very quickly and is capable of arousing very strong emotions. According to Rangkuti & Lubis (2018), problems that can threaten the integrity of the nation do not only come from differences in political-ideological attitudes but can come from language impoliteness. Therefore, this paper aims to develop an analysis model of impolite Indonesian language use (Pinker & Prince, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…This condition has destructive power because it spreads very quickly and is capable of arousing very strong emotions. According to Rangkuti & Lubis (2018), problems that can threaten the integrity of the nation do not only come from differences in political-ideological attitudes but can come from language impoliteness. Therefore, this paper aims to develop an analysis model of impolite Indonesian language use (Pinker & Prince, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Then, there were 70 contents were removed, 179 submitted for blocking, and 67 more still pending. According to Rangkuti and Lubis [3], problems that can threaten the integrity of the nation do not only come from the differences in political ideological attitudes, but can also come from language impoliteness. This paper focuses on the form of language impoliteness in the Facebook status account as the social media most given warning.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, impoliteness strategies of hate speech quite often found in social media and the regulations regarding hate speech has been implemented by the government of Indonesia [2]. The problem of impoliteness is commonly found in Indonesia as multicultural society [3]. Some previous research conducted by [4] in her analysis found that the positive impoliteness was the dominant type found in politician instagram account.…”
Section: Introductionmentioning
confidence: 99%